Nuno Ramos and clashes between languages: visual works from which the literal work (and vice versa) (Palíndromo, 2015)
In this study we checked the literary work Cujo (1993), Nuno Ramos (1960), some impressions of his visual work in the same decade. As a studio record, whose becomes a means to Nuno Ramos express himself as a visual artist (as in a daily report) and as a narrator (through metaphorical passages) to describe and translate own aesthetic profundity procedure and artistic and conceptual creation. By aforismática writing, Nuno Ramos leads us to think about the possible match between literary narrati- ve and matter-specific concentrated in the visual compositions - even if ephemeral and hybrid. The voices of Nuno Ramos empha- size a “transmutation” process, ie, a “trans- lation intersemiotic” that opposes linguistic signs to other types of signs, approaching in this way words and “things” and creating the effect of narratives about the material issues of the world.
Keywords: visual art; literature; sing; body [; contemporaneity